(untitled) (Research Journal of Padmakanya Multiple Campus, 2024)
The perception of people living nearby river flow differs from the people, particularly, the policy makers, who live far away from the river. The river basins are natural corridors which are increasingly in pressure from development activities, especially hydropower in Mountain region. It’s very difficult to know about idea of local people toward the use of flow regime in the basin area. The existing knowledge on the use of flow regime is difficult to understand and few studies have been done on the interaction between river flow and adjoining settlements. The aim of this paper is to assess perception of local people towards ecological flow (e-flow) and overall flow diversion based on FGD. In such state, spatial understanding of these activities isuseful for planning and understanding its interaction. The researcher had not found any changes in the issues for the last one decade spatially and temporarily. The present study was conducted in the Tamakoshi River Basin during 2014 and 2015. It concludes that there is strong relationship between use of flow water and riparian settlement with fishing, graveling, sand extracting, which contribute to ecological condition and share expectation. The expectation of obtaining hydropower shares (IPO) is increasing but majority of them are unaware about long term ecological disruption. If this trend continues along the river basin, many of the settlements from the upper part to middle part will expect IPO shares. The interaction with people highlights major opinion that the flow disruption is good for the power production, but long run impact must be taken into consideration and this article will make a valuable suggestion towards policy level.